Determination of the size of small particles by light scattering - Velazco, Abner (2017)
In this work, we describe the design and construction of a system to measure the angular light scattering distribution from small dielectric spheres suspended in water, using a laser as the light source. It also covers the development of an optical detection system to improve the signal‐to‐noise ratio. We report on the experimental measurements of light scattering from colloidal suspensions of latex spheres with nominal diameters of 0.49 and 1.03 µm and a coefficient of variation of 3%. Two lasers with different wavelengths (632.8 and 532.0 nm) were used to observe the variation of the angular scattering distribution. The experimental results were then compared with angular scattering distributions generated from Mie theory, in order to determine the particle size. We obtained diameters of 0.49 and 0.95 µm, with a relative accuracy of 6.1 and 5.3%, respectively.